Chondromyxoid Fibroma of the Frontal Bone Mimicking Meningioma. Issue 2 (March 2015) - Wang, Hao; Shu, Hansheng; Tian, Xuping; Zhang, Hui; Zhang, Qiujian; Guo, Liemei
<x xml:space="preserve">Abstract</x> Abstract Chondromyxoid fibroma (CMF) is a rare benign cartilaginous tumor that usually arises from lower-extremity long-bone metaphyses, with approximately 5.4% of all CMFs presenting in the craniofacial bones. Chondromyxoid fibroma of the frontal bone is exceedingly rare, with only a few cases reported. Herein, we report another case of CMF arising from the frontal bone mimicking meningioma. We suggest that histopathologic examination is of vital importance for the diagnosis of CMF; complete surgical resection is the best treatment option for frontal CMF.